Photodynamic Activity of Plant Extracts from Sarawak, Borneo. Issue 8 (12th August 2013) - Jong, Wan Wui; Tan, Pei Jean; Kamarulzaman, Fadzly Adzhar; Mejin, Michele; Lim, Diana; Ang, Ida; Naming, Margarita; Yeo, Tiong Chia; Ho, Anthony Siong Hock; Teo, Soo Hwang; Lee, Hong Boon
Abstract Photodynamic therapy (PDT) is a medical treatment that involves the irradiation of an administered photosensitizing drug with light of a particular wavelength to activate the photosensitizer to kill abnormal cells. To date, only a small number of photosensitizers have been clinically approved for PDT, and researchers continue to look for new molecules that have more desirable properties for clinical applications. Natural products have long been important sources of pharmaceuticals, and there is a great potential for discovery of novel chemotypes from under‐explored biodiversities in the world. The objective of this study is to mine the terrestrial plants in Sarawak, Borneo Island, for new photosensitizers for PDT. In a screening program from 2004 to 2008, we prepared and studied 2, 400 extracts from 888 plants for their photosensitizing activities. This report details the bioprospecting process, preparation and testing of extracts, analysis of the active samples, fractionation of four samples, and isolation and characterization of photosensitizers.